2019
DOI: 10.1111/jai.13929
|View full text |Cite
|
Sign up to set email alerts
|

Administration of host‐derived probiotics does not affect utilization of soybean meal enriched diets in juvenile turbot (Scophthalmus maximus)

Abstract: In today's aquaculture, the cost‐intensive and scarce fishmeal is increasingly replaced by plant‐based feedstuff such as soybean meal (SBM). However, SBM contains saponins which can have adverse effects on fish's digestive tract potentially culminating in severe enteritis. In a 60 day feeding trial we studied the use of autochthonous bacteria as probiotics upon SBM supplementation on juvenile turbot. Growth performance, feed conversion, body composition and health status were assessed for five different treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 65 publications
(147 reference statements)
1
3
0
Order By: Relevance
“…Even though the condition factor (CF) of turbot from the PLANT group showed statistically a difference to the control and PAP group (2.07 vs. 2.11 and 2.10, respectively), the physiological relevance is minor and does not indicate poorer nutritional status. CFs above 2 indicate an overall good nutritional status of the fish, as presented CFs are similar to values of in previous studies (Fuchs et al 2015;Nagel et al 2017;von Danwitz et al 2016;Wanka et al 2019;Weiß and Buck 2017). In previous studies, a reduced CF was observed in turbot fed with plant-based diets (Bonaldo et al 2015) and insect meal-based diets (Kroeckel et al 2012) at a substitution/replacement level of more than 55%.…”
Section: Growth and Feed Performancesupporting
confidence: 88%
See 1 more Smart Citation
“…Even though the condition factor (CF) of turbot from the PLANT group showed statistically a difference to the control and PAP group (2.07 vs. 2.11 and 2.10, respectively), the physiological relevance is minor and does not indicate poorer nutritional status. CFs above 2 indicate an overall good nutritional status of the fish, as presented CFs are similar to values of in previous studies (Fuchs et al 2015;Nagel et al 2017;von Danwitz et al 2016;Wanka et al 2019;Weiß and Buck 2017). In previous studies, a reduced CF was observed in turbot fed with plant-based diets (Bonaldo et al 2015) and insect meal-based diets (Kroeckel et al 2012) at a substitution/replacement level of more than 55%.…”
Section: Growth and Feed Performancesupporting
confidence: 88%
“…Interestingly, it has been shown that the reduction and replacement of fishmeal with alternative feed ingredients could lead to contradicting results. Decreasing fishmeal content may lead to a decreased HSI (Bai et al 2019;Gu et al 2017;Kroeckel et al 2012;von Danwitz et al 2016;Wanka et al 2019), unchanged HSI (Bonaldo et al 2015;Fuchs et al 2015;Wang et al 2016;Weiß and Buck 2017) or even increased HSI (Dietz et al 2012;Fournier et al 2004;Nagel et al 2017). This aspect might be worth investigating in more detail to unravel the observed variation in HSI, hepatic glycogen and lipid dependent on alternative feed ingredients.…”
Section: Nutritional and Energy Statusmentioning
confidence: 99%
“…Previous findings indicate that the use of multistrain probiotics improves functionality and efficacy. Provided that mutual inhibition can be excluded, the combination of multiple beneficial isolates is recommended [75][76][77].…”
Section: Species-specific Native Probioticsmentioning
confidence: 99%
“…At final sampling, the condition factor (CF) of the individually tagged fish from the PAP60 (1.9) group was significantly lower compared to the fish from the CTRL group (2.0). The difference is very small and the CFs presented in the fish from all groups is considered as normal (Fuchs et al, 2015;von Danwitz et al, 2016;Nagel et al, 2017;Weiß and Buck, 2017;Wanka et al, 2019), whereas turbot strains from France appear to have a lower CF (Imsland et al, 2000;Arfsten et al, 2010). In smaller turbot the CF was reduced at FM replacement levels of 45% by fermented soybean and blood meal in turbot (Dan et al, 2021;Zheng et al, 2022) more than 55% with plantbased diets (Bonaldo et al, 2015) and insect meal-based diets (Kroeckel et al, 2012).…”
Section: Performance Of the Sustainable Formulations Concepts In Comp...mentioning
confidence: 99%